Dinâmica das transformações de intercâmbio de intervalos - Nosaki, Gregório Luís Dalle Vedove [UNESP] (2015)
In this work we are interested in the dynamics of intervals exchange transformations. In this context we study the Rauzy- Veech renormalization process and some consequences. Finally we analyze the relationship between the intervals exchange transformations and homeomorphisms on the circle where we prove the convergence of the renormalization operator in the case of piecewise smooth homeomorphisms on the circle